Telipogon crisariasae (Orchidaceae) a new species from northen Ecuador - Baquero R., Luis E.; Iturralde, Gabriel A.; Martel, Carlos (Phytotaxa, 2022)
Telipogon crisariasae, discovered in northern Ecuador, is described as a new species. Telipogon crisariasae is similar to T. octavioi but differs by its larger inflorescences and flowers, the rhomboid petals, the cordiform pink callus, and the sub-trapeziform stigmatic cavity. Illustrations and pictures of the new entity are provided. Furthermore, diagnostic characters of T. crisariasae are compared to those of other morphologically similar species.